Effectiveness of Digital-Based Public Service Innovation: Case Study of Population Services in Indonesia’s Local Government - Al - Muttaqin, Febrian Akhmad; Nugroho, Rino Ardhian (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2025)
This study investigates the effectiveness of a digital-based public service innovation targeting non-permanent population management in the Surakarta City Government, Indonesia. Using a qualitative descriptive approach, including interviews, field observations, and document analysis, the study assesses the program’s accuracy, public outreach, goal attainment, and monitoring mechanisms. The results show that the program has significantly improved data collection and service delivery for non-permanent residents, offering both online and offline registration channels. Key outcomes include shortened processing times for population-related documents and improved data integration within the local civil registry system. However, technical limitations of the digital platform and disparities in digital literacy among users present persistent challenges. This research illustrates the critical role of digital governance in enhancing public service delivery at the regional level. It emphasizes the importance of inclusive technological infrastructure, community digital readiness, and sustained administrative support in ensuring effective service outcomes. The case offers practical insights into how digital innovation can be adapted to local governance contexts in developing countries, contributing to broader discussions on administrative reform and citizen-oriented policy implementation.